2013
DOI: 10.1155/2013/453835
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Oxidation Behavior of Yttria Stabilized Zirconia Coating on Zircaloy-4 Synthesized via Sol-Gel Process

Abstract: Sol-gel 8 wt.% Yttria Stabilized Zirconia (YSZ) thin films were prepared on zirconium (zircaloy-4 alloy) by dip-coating technique followed by heat treating at various temperatures (200°C, 400°C, and 700°C) in order to improve both electrochemical corrosion and high temperature oxidation properties of the substrate. Differential thermal analysis and thermogravimetric analysis (DTA-TG) revealed the coating formation process. X-ray diffraction (XRD) was used to determine the crystalline phase structure transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…The crystallite size, which is given by the width of the diffraction line, was of 70 Å. Similar results have been reported and show the peaks in 2θ characteristics of YSZ and ZrO 2 [15][16][17]]. …”
Section: Ysz8 N Characterizationsupporting
confidence: 84%
“…The crystallite size, which is given by the width of the diffraction line, was of 70 Å. Similar results have been reported and show the peaks in 2θ characteristics of YSZ and ZrO 2 [15][16][17]]. …”
Section: Ysz8 N Characterizationsupporting
confidence: 84%
“…In stage I, which ranged from room temperature up to approximately 220 °C, a weight loss of ~15% was observed. This weight loss has been associated with the vaporization of superficial and structural water [19,[25][26][27][28]. The stage II, which ranges from 220 to 350 °C, with a weight loss of 19%, has been associated with the combustion and decomposition of organic compounds [19,26,[28][29][30].…”
Section: Effect Of Yttria Concentration and Sintering Timementioning
confidence: 99%
“…However, a common feature associated with the deposition of YSZ thin films and coatings through sol-gel/dip-coating is the production of materials with cracks or defects if the heat treatment or deposition conditions are not controlled [3,[14][15][16]. For example, it has been observed that coatings thicker than 200 nm are prone to cracking due to the release of gases, thermal mismatch between the coating and the substrate, and internal stresses during heat treatment [17][18][19]. Crack formation can be reduced or avoided by controlling the sol-gel fabrication route (for example, using complexing agents affecting the hydrolysis and condensation reactions or by modifying the viscosity of the gel), the extraction rate, and heat treatment temperature or by depositing several consecutive coatings for the purpose of filling the cracks that are generated [14,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, al someter el recubrimiento a un tratamiento térmico se logra una superficie libre de grietas y con mejores propiedades anticorrosivas. Se ha trabajado especialmente con estructuras cristalinas estabilizadas con itria [6,[12][13][14]. Sin embargo, una de las alternativas para obtener películas con fines de protección anticorrosiva podría ser el uso de zirconia estabilizada con calcia, que resulta en un compuesto (CaZrO3) más estable químicamente y con buena resistencia a la corrosión que hasta el momento parece no haber sido estudiado sobre sustratos de acero inoxidable y aluminio comercial.…”
Section: Introductionunclassified